To What Extent does CRISPR/Cas9 Truly Elevate Target Efficiency and Revolutionize Drug Discovery? - Gao, Leyao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The emergence of the CRISPR/Cas9 system has ushered in a new era of genetic editing with vast implications for both therapeutic interventions and drug discovery. This essay explores the extent to which CRISPR/Cas9 elevates target efficiency and revolutionizes drug discovery. While this technology offers unprecedented efficiency, precision, and programmability in genome editing, concerns about off-target effects have arisen. The essay discusses the transformative impact of CRISPR/Cas9 in drug discovery, particularly in cancer research and combating antimicrobial resistance. It also highlights strategies for detecting and mitigating off-target effects, such as in silico prediction tools, experimental methods, and precision-enhancing techniques. Ultimately, CRISPR/Cas9’s potential is undeniable, but its full realization depends on ongoing research and refinement to optimize specificity and revolutionize the field of drug discovery.